Biomechanical Behavior of Different Miniplate Designs for Skeletal Anchorage in the Anterior Open Bite Treatment - Ielpo, Ana Paula Macarani [UNESP]; de Matos, Jefferson David Melo [UNESP]; Noritomi, Pedro Yoshito; da Rocha Scalzer Lopes, Guilherme [UNESP]; Queiroz, Daher Antonio; Borges, Alexandre Luiz Souto [UNESP]; Nascimento, Rodrigo Dias [UNESP] (MDPI, 2022)
This study aimed to evaluate the stress distribution and mechanical behavior of miniplate designs to skeletal anchorage for the treatment of anterior open bite in adult patients. A complete hemimaxilla, teeth, brackets, transpalatal bar, and three miniplates were virtually modeled. I-, Y-, and T-shaped miniplates were installed in the area of the alveolar zygomatic crest. The assembly was constricted and three intrusive forces (2, 4, and 6 N) were applied to the maxillary molars and anchorage according to the miniplates. All materials were considered homogeneous, elastic, and linear; the mesh was 1,800,000 hexahedrons with 2,800,000 nodes on average. Displacement, maximum principal stress, and von Mises stress were evaluated according to the shape of the anchorage device and intrusive force. The miniplate configurations resulted in different stress and displacement intensities in the bone tissue and plate; these stresses were always located in the same regions and were within physiological limits. The Y-plate showed the best performance since its application generated less stress in bone tissue with less displacement.
Keywords: anterior open bite; miniplates; orthodontic anchorage